Equity stakes and exit: An experimental approach to decomposing exit delay - Elfenbein, Daniel W.; Knott, Anne Marie; Croson, Rachel (Strategic Management Journal, 2017)
Research summary : Exit delay is an important problem for entrepreneurs and managers alike, yet relatively little is known about its causes. We conduct a laboratory experiment in which optimal exit is well defined, and in which a treatment group with equity stakes—the actual cash flows of a firm and decision rights over its continuation—is compared to a control group whose compensation is based solely on its assessment of the firm's profitability. While treatment group participants make exit decisions that are nearly optimal given their beliefs, their beliefs are significantly distorted relative to the control group. The pattern of distortion is consistent with confirmatory bias and motivated reasoning. A fundamental finding of our study is that incentives may not only affect behavior, but belief formation as well . Managerial summary : Managers and entrepreneurs frequently destroy significant value by failing to shut down underperforming businesses in a timely manner. To address this problem, we must understand the mechanisms causing exit delay. We examine behavioral mechanisms causing delay through a laboratory experiment in which subjects make decisions about when to exit a failing venture. We find that “equity stakes”—receiving the firm's cash flows and having decision rights over exit—cause participants to discount negative performance information, retain overly optimistic beliefs, and delay exit. By contrast, participants without these high‐powered incentives exit nearly optimally. Our findings suggest ways to reduce exit delay in managerial settings, including implementing automated decision rules, removing equity‐based compensation, and recruiting managers less susceptible to knowledge overconfidence, a trait associated with exit delay . Copyright © 2015 John Wiley & Sons, Ltd.